Pemasaran Semangka (Citrullus Lanatus) di Desa Waihatu Kecamatan Kairatu Barat Kabupaten Seram Bagian Barat - Moh. Rahmad Santoso; Martha Turukay; Fioletta Papilaya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
In marketing, watermelon will undergo a marketing process and experience changes in prices at the producer level and prices at the end consumer, resulting in differences in the price of watermelon between producers and consumers. This makes marketing a very important activity. The aim of this research is to determine marketing channels, margins and marketing efficiency. The population in this study was 140 watermelon farmers. The sample was determined using the Slovin method, so that the selected respondents were 34 watermelon farmers and the sample of trader respondents was 5 people, namely 2 village collectors, 1 wholesaler and 2 retailers. The analytical tools used are descriptive analysis, margin analysis and efficiency analysis. The research results show that there are 2 marketing channel patterns for watermelon in Waihatu Village, namely: marketing channel I farmer-retailer-final consumer, while marketing channel II farmer-village collector-wholesaler-retailer-final consumer. The highest total marketing margin is in marketing channel I, namely IDR 2,000/kg, while the lowest total margin is in marketing channel II, namely IDR 1,000/kg. In conclusion, both marketing channels are classified as efficient, marketing channel II with an efficiency value of 12.21 percent and marketing channel I with the smallest efficiency value, namely 3.34 percent.